Hypertension in Hypoxia - Sheetal Chawla; Rashi Singhal; Prasenjit Guchhait (Journal of Hypertension and Cardiology, 2014)
An overview of blood pressure regulation in hypoxia addresses altitude physiology, sleep disordered breathing, and cardiopulmonary disease. It reviews pathophysiology and therapeutic implications.
Keywords: hypertension